Factors associated with non-adherence to medication in hypertensive patients: baseline assessment of the ESSENCE study - Canguçu, Erlan; Castro, Priscila; Moreira, Pablo; Bandeira, Paola; Coelho de Almeida, Kleiton; Oliveira, Márcio (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objective: to evaluate factors associated with therapeutic adherence among hypertensive patients treated at a community pharmacy. Methods: A descriptive secondary analysis of the baseline data from the ESSENCE study, which included hypertensive patients aged 30 to 69 years, followed up at a community pharmacy. Sociodemographic and clinical variables were evaluated as possible predictors of medication adherence. Adherence was measured using the Brief medication Questionnarie (BMQ), and the variables of interest were collected through interviews. Results: A total of 160 patients were evaluated, with 76.6% being female and an average age of 53 years (± 9.08). A 59.4% adherence rate to antihypertensive treatment was found. Among the variables evaluated as predictors, only the total number of medications used (p≤0.001) and the number of daily doses in the therapeutic regimen (p-value = 0.029) showed a statistically significant association. Conclusion: The findings highlight the need to develop strategies aimed at simplifying therapeutic regimens to promote medication adherence.